GEOGRAPHIC INFORMATION SYSTEM (GlS) SEBAGAI SUATU SISTEM YANG MEMBANTU PENGAMBILAN KEPUTUSAN MANAJEMEN KHUSUSNYA DALAM PENENTUAN LOKASI - Sandra Sunanto (Center for Economic Studies Universitas Katolik Parahyangan, 2000)
Geographical information system (GIS) is a tool for management to support their decision making about location. This system integrates geographical data and demographic data to decide the location of potential services unit. With a huge opportunity to develop speed and accuracy of handling geographical data, GIS can make this data be applied for another kind of managerial and social issues the future challenge is how we can optimize this system for developing company's value and mission.